Remaja dan Narkotika: Pengaruh Hukum dalam Perilaku Penyalahgunaan - Dayan, Mhd. Rahmani (Universitas Islam Sumatera Utara, 2024)
Abuse of drug abuse among adolescents is a serious problem that has a wide impact on physical, mental, and social health. This study aims to explore the influence of the law on drug abuse behavior among adolescents. among adolescents. Using mixed methods, namely in-depth interviews and surveys, this study collected data from teenagers in several schools in Medan City and relevant professionals. The results showed that adolescents have a limited understanding of the legal consequences of drug drug abuse, and strict legal sanctions are often ineffective in preventing use. in preventing use. In addition, social stigma and lack of access to to rehabilitation programs are barriers to addressing this issue. These findings emphasize the need for a more holistic approach, including better education about drugs and the law, as well as the development of supportive rehabilitation programs. supportive rehabilitation programs. By understanding the relationship between the law and adolescent behavior, it is hoped that more effective solutions can be found for address drug abuse among young peopleKeywords: Teenagers, Narcotics, Behavior